# What is the equation of the tangent line of #f(x)=e^(-x^2)-x^2e^x# at #x=4#?

using the chain rule:

using the product rule:

By signing up, you agree to our Terms of Service and Privacy Policy

The equation of the tangent line of f(x)=e^(-x^2)-x^2e^x at x=4 is y = -32e^(-16) + 32e^(-16)(x-4).

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- What is the equation of the normal line of #f(x)=5x^3-2x^2-3x-1# at #x=-8#?
- Using the limit definition, how do you find the derivative of #f(x) = -5x^2+8x+2#?
- How do you find the slope of the secant lines of # f(x) = x^2 + 5x# at (6 , f(6)) and (6 + h , f(6 + h))?
- What is the equation of the line tangent to #f(x)=x ^3-3x^2 # at #x=4#?
- What is the average rate of change of the function #f(z) = 2-5(z^2)# on the interval [-7,2]?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7